Changes in epidemiological patterns of sea lice infestation on farmed Atlantic salmon, Salmo salar L., in Scotland between 1996 and 2006 - Lees, F (Journal of fish diseases, 2008)
Analyses of a unique database containing sea lice records over an 11 year period provide evidence of changing infestation patterns in Scotland. The data, collected from more than 50 commercial Atlantic salmon farms, indicate that both species of sea lice commonly found in Scotland, Lepeophtheirus salmonis and Caligus elongatus, have declined on farms over the past decade. Reductions for both species have been particularly marked since 2001 when more effective veterinary medicines became available. Treatment data were also available in the database and these show a growing trend towards the use of the in-feed medication emamectin benzoate (Slice), particularly in the first year of the salmon production cycle. However, this trend towards single product use has not been sustained in 2006, the latest year for which data are available. There is some evidence of region to region variation within Scotland with the Western Isles experiencing higher levels of infestation. However, compared to the levels observed between 1996 and 2000, all regions have benefited from reduced lice infestation, with the overall pattern showing a particular reduction in the second and third quarters of the second year of production